(untitled) (Bangladesh Journal of Medical Microbiology, 2018)
Clostridium difficile (C. difficile) has become a global public health challenge as C. difficile associated-diarrhea (CDAD) is increasing in incidence and severity of disease in several countries during recent years. This cross sectional study evaluated the frequency of CDAD among 100 adult patients who were clinically diagnosed as nosocomial diarrhoea in various clinical wards of Bangabandhu Shiekh Mujib Medical University (BSMMU) and Dhaka Medical College and Hospital (DMCH). CDAD diagnosis was based on detection of C. difficile along with clinical symptoms of diarrhea. Stool microscopy was done for cytology followed by anaerobic culture in cycloserine cefoxitin fructose agar (CCFA) media, confirmed by latex agglutination of culture isolates. Toxin genes (both A and B) were detected by multiplex Polymerase chain reaction (PCR) from culture isolates. Out of 100 diarrhoeal stool samples collected, 25% samples were pus cell positive in microscopy, culture yielded growth of C. difficile in 10% samples and all isolated C. difficile were confirmed by both latex agglutination and PCR. Out of 10 isolates, 7 were only tpi (triose phosphate isomerase) gene positive which is species-specific for C. difficile indicating the presence of non-toxigenic C. difficile and 3 isolates had both tpi and toxin genes (both tcdA and tcdB gene) on PCR indicative of toxigenic C. difficile respectively. C. difficile toxin gene detection by PCR along with culture is highly specific and sensitive diagnostic modality for CDAD. Differentiation between toxigenic and non-toxigenic strains by PCR may facilitate the appropriate patient management. Bangladesh J Med Microbiol 2018; 12 (1): 4-9